May B. : a novel - Rose, Caroline Starr. (Schwartz & Wade Books, 2012)
When a failed wheat crop nearly bankrupts the Betterly family, Pa pulls twelve-year-old May, who suffers from dyslexia, from school and hires her out to a couple new to the Kansas frontier.